EFFECT OF FISCAL DECENTRALIZATION ON ECONOMIC GROWTH OF REGENCY/CITY IN EAST JAVA 2010-2014 - Syifa Habibah; Haryo Kuncoro; Karuniana Dianta (Fakultas Ekonomi Universitas Negeri Jakarta, 2017)
This study aims to determine whether the Fiscal Decentralization that measured by revenue capacity and expenditure capacity have an impact on economic growth in East Java 2010-2014. The research method used in this study is shaped Time Series of the 2010-2014 and the cross section amounts to 12 regency and 4 city in East Java Province, with ex post facto method. The data presented annually obtained from BPS (Central Bureau of Statistics) of the Ministry of financial. This study uses panel data regression model Fixed effect. Based on the results of simultaneous analysis, revenue capacity and expenditure capacity significantly influence on economic growth of 16 regency/city in East Java. Based on the results of the analysis the revenue capacity giving impact significantly positive on economic growth of 16 regency/city in East Java. The expenditure capacity have negative impact and significant to economic growth of 16 regency/city in East Java.